Fundamental Investigation on a Foam-Generating Microorganism and Its Potential for Mobility Reduction in High-Permeability Flow Channels - Miu Ito; Yuichi Sugai (Energies, 2022)
This study proposed a novel foam EOR technique using Pseudomonas aeruginosa to generate the foam and investigated the potential of the microbial foam EOR to modify the permeability of a high-permeability porous system. We investigated oxygen nanobubble, carbon dioxide nanobubble and ferrous sulfate concentrations to discover the optimal levels for activating the foam generation of the microorganism through cultivation experiments. We also clarified the behavior of the microbial foam generation and the bioproducts that contribute to the foam generation. The potential of the foam to decrease the permeability of high-permeability porous systems was evaluated through flooding experiments using sand pack cores. The foam generation became more active with the increase in the number of nanobubbles, while there was an optimal concentration of ferrous sulfate for foam generation. The foam was identified as being induced by the proteins produced by the microorganism, which can be expected to bring about several advantages over surfactant-induced foam. The foam successfully decreased the permeability of high-permeability sand pack cores to half of their initial levels. These results demonstrate that the microbial foam EOR has the potential to decrease the permeability of high-permeability porous systems and improve the permeability heterogeneity in oil reservoirs.